2018
DOI: 10.1103/physrevd.97.076002
|View full text |Cite
|
Sign up to set email alerts
|

Photon-photon scattering at the high-intensity frontier

Abstract: The tremendous progress in high-intensity laser technology and the establishment of dedicated high-field laboratories in recent years have paved the way towards a first observation of quantum vacuum nonlinearities at the high-intensity frontier. We advocate a particularly prospective scenario, where three synchronized high-intensity laser pulses are brought into collision, giving rise to signal photons, whose frequency and propagation direction differ from the driving laser pulses, thus providing various means… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 110 publications
(115 reference statements)
1
35
0
Order By: Relevance
“…In order to use the high-energy approximation Eq. ( 27) for the QED calculation with the paraxial Gaussian beam, we employ the infinite Rayleigh-length approximation [124,125] (no such approximation is required in the simulation), which sends ς → 0, meaning that a ⊥ can be written as a ⊥ = exp[−(x ⊥ ) 2 /w 2 0 ]a ⊥ pw where a ⊥ pw is the plane-wave potential. We pick the same pulse envelope as in previous sections, i.e.…”
Section: Focused Lasersmentioning
confidence: 99%
“…In order to use the high-energy approximation Eq. ( 27) for the QED calculation with the paraxial Gaussian beam, we employ the infinite Rayleigh-length approximation [124,125] (no such approximation is required in the simulation), which sends ς → 0, meaning that a ⊥ can be written as a ⊥ = exp[−(x ⊥ ) 2 /w 2 0 ]a ⊥ pw where a ⊥ pw is the plane-wave potential. We pick the same pulse envelope as in previous sections, i.e.…”
Section: Focused Lasersmentioning
confidence: 99%
“…In addition, the presence of magnetic fields produce an enhancement at the light shinning through wall experiments designed in [28,29], which may be seen in a near future. Further applications of these non linearities for laser fields were considered in [40]. In addition, the interaction between micro-bubbles with ultra intense laser pulses, by taking into account the QED vacuum polarization, was studied in [56].…”
Section: Further Comments About the Approximations Madementioning
confidence: 99%
“…A solution for this challenge is to combine the highest achievable electric field from laser pulses with ultra-relativistic electron beams or γ-photons, allowing the Schwinger field to be achieved in the rest frame of the electrons. In addition to pair generation, the vacuum responds nonlinearly and processes such as light-light scattering [10] and vacuum birefringence [11] can occur and be detected [12]. A review of strong-field QED processes is found in reference [3].…”
Section: Introductionmentioning
confidence: 99%